Development of Blended Learning Model Based Jigsaw to Enchance Science Motivation College Students - Oktaria, Sheren Dwi; Badeni, B; Alexon, A (Universitas Muhammadiyah Surakarta, 2022)
The purpose of this research is to produce a quality jigsaw-based Blended learning model to increase science motivation. This development research adopts the development step with the ADDIE model which consists of the Analysis, Design, Develop, Implement and Evaluate stages. Data collection was obtained through internal validation and external validation. This development research produces a product in the form of a blended learning model based on the components and devices of the learning model. Student science motivation gave a good response and had an impact on increasing learning motivation such as intrinsic motivation, self-efficacy, self-determination, grade motivation, and career motivation with an average of 3.36 in the very good category.